Aorta-Right Atrial Tunnel: An Interesting Type of a Congenital Coronary Artery Anomaly - Iyisoy, Atila (The Korean Society of Cardiology, 2014)
An 18-year-old girl with an aortico-right atrial tunnel originating from the left sinus of Valsalva, in which the left anterior descending and circumflex coronary arteries arose independently from the different parts of the tunnel, was reported. In the differential diagnosis of continuous murmur, this type of tunnel should be taken into consideration. Surgical approach should be offered.